1978
DOI: 10.1002/tera.1420170205
|View full text |Cite
|
Sign up to set email alerts
|

Congenital central nervous system malformations and vinyl chloride monomer exposure: A community study

Abstract: Incidence rates for central nervous system (CNS) malformations in infants born to residents of Kanawha County, West Virginia, 1970-1974, were significantly higher than comparable United States rates during those years. Since Kanawha County contains a polyvinyl chloride (PVC) polymerization plant, a case-control study was conducted on the possible relationship between the occurrence of CNS defects and parental occupational or residential exposure to vinyl chloride monomer emissions from this plant. No relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…These studies grew out of suggestions that central nervous system malformation rates were high in communities with polyvinyl chloride polymerization plants (36). Studies in West Virginia (37) and Quebec (38) tested the suggested relationship using case-control studies and failed to demonstrate statistically significant associations. A more recent study in New Jersey found increased odds ratios for central nervous system defects in proximity to two vinyl chloride polymerization facilities, but the increases were not statistically significant (39).…”
Section: The Environment and Neural Tube Defectsmentioning
confidence: 99%
“…These studies grew out of suggestions that central nervous system malformation rates were high in communities with polyvinyl chloride polymerization plants (36). Studies in West Virginia (37) and Quebec (38) tested the suggested relationship using case-control studies and failed to demonstrate statistically significant associations. A more recent study in New Jersey found increased odds ratios for central nervous system defects in proximity to two vinyl chloride polymerization facilities, but the increases were not statistically significant (39).…”
Section: The Environment and Neural Tube Defectsmentioning
confidence: 99%
“…However, Pearn (63) noted that there is, to date, no experimental evidence to suggest that paternal exposure to agents can result in a teratogenic effect. Neither paternal nor maternal preconceptional occupational exposures have been extensively examined with regard to the risk of malformations in offspring (5,6,14,18,20,21,52,77,78,85). On the other hand, much more is known about how postconceptional occupational exposures may affect normal embryologic development (2, 7, 16, 22-24, 29, 30, 34-36,45, 47, 48, 50, 55, 59, 72).…”
Section: Biological Considerations Of Occupational Exposuresmentioning
confidence: 99%
“…Data in the CDC's Birth Defects Monitoring Program suggested higher rates of central nervous system defects in some counties with vinyl chloride industrial plants. Further study failed to establish an association with parental exposure (26). Data from US monitoring systems were used to correlate sales of spray adhesives with birth defect rates; no correlation was found (32b).…”
mentioning
confidence: 99%